Peranan Kepala Sekolah dalam Meningkatkan Potensi Berorganisasi Peserta Didik di MI NW Keruak - M. Saipul Watoni; Ema Dara Sista; Sulistianing; Maharani (Al-Gafari : Manajemen dan Pendidikan, 2024)
The principal as a leader in an educational institution has a very dominant role in improving the quality of education, therefore a professional principal is needed who is able to manage all school resources so that they can function well, to support the achievement of the expected school goals. This research was conducted to know the planning and implementation of the Principal in increasing the potential for organizing students in Keruak MI NW and how to evaluate The principal in expanding the potential for organizing students in MI NW Keruak. This type of research is descriptive qualitative research, namely data collected in words, and images, not numbers. The research subjects were the principal of MI NW Keruak. This study emphasizes the role of the school principal in improving or developing organizations or extracurricular activities at school. The data collection technique uses observation, interviews, and documentation methods, then processed with descriptive analysis to describe every data obtained. Based on data analysis in the field can be explained that the planning of the principal in attracting students to be motivated in organizing in MI NW Keruak, namely a principal must be required to be an inspiration, motivator, and collaborator. The process of increasing the potential for organizing students who have committed school principals, namely: good managerial and structural management, student management in increasing interest and organizational potential, management of education and education personnel in expanding the potential for organizing students, management Facilities and infrastructure in increasing the potential of students, financing management in expanding the potential for organizing students and environmental management. The evaluation carried out by the Principal in expanding the potential for organizing students in the MI NW Keruak, which is done through several steps, namely: Monitoring student participation in organizational activities, assessing the effectiveness of extracurricular programs that support the development of student organizational skills, self-assigning regular meetings with students to listen to their input about the needs and expectations related to the organization of students, evaluating the progress of students in achieving the objectives of the organization that have been determined, encouraging student leadership through training and glance and conducting surveys or interviews with students to get feedback about their experience in organizing in school.